2019
DOI: 10.1089/met.2018.0115
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Reduction of 5% Improved Blood Pressure and Lipid Profiles in Obese Men and Blood Glucose in Obese Women: A Four-Year Follow-up Observational Study

Abstract: Background: Body weight reduction (BWR) of at least 3% in obese Japanese individuals through lifestyle interventions has improved the risk factors for cardiovascular disease (CVD). We aimed to assess the relation between body weight change (BWC) and CVD risk change and to identify lifestyle improvement related to BWR in obese Japanese individuals. Methods: Subjects were 2579 health checkup examinees without medicated diabetes, hypertension or dyslipidemia, and a body mass index ‡25 kg/m 2 who completed lifesty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Similar opinions have also been claimed in another study by Truesdale et al [ 43 ]. Previous longitudinal studies mainly focused on changes in weight or WC in relation to incident dyslipidemia [ 2 , 44 ] or lipid profiles [ 20 , 36 , 42 , 45 , 46 ]. Here, we mainly focused on changes in WHtR and BMI because it was important to distinguish the risk of different subjects by taking height into account when they have comparable weight or WC changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar opinions have also been claimed in another study by Truesdale et al [ 43 ]. Previous longitudinal studies mainly focused on changes in weight or WC in relation to incident dyslipidemia [ 2 , 44 ] or lipid profiles [ 20 , 36 , 42 , 45 , 46 ]. Here, we mainly focused on changes in WHtR and BMI because it was important to distinguish the risk of different subjects by taking height into account when they have comparable weight or WC changes.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity-induced dyslipidemia has been identified as “metabolic-related dyslipidemia” [ 49 ], which is mainly driven by the effects of insulin resistance and proinflammatory adipokines [ 10 ]. Abundant evidence supports that weight loss is conducive to the improvement in lipid profile measures [ 46 , 50 ]. As an essential modifiable risk factor of CVD, systematic health education and early interventions should be recommended to help individuals with the above risk factors to lose weight and reduce CVD risk, especially among the Chinese population in the context of rapid economic development and shifting lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…A 4-years follow-up observational study conducted in Japan found that body weight reduction could improve lipid levels in men. Improvements in physical activity have been associated with body weight reduction ( 30 ). Regular exercise is regarded as an important part of health optimization and longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated weight loss to be effectively instrumental in decreasing high blood pressure in obese individuals. In the study combined with a four-year follow-up, as conducted by Hasegawa et al [ 45 ] in a population of 2579 Japanese individuals with BMI ≥ 25 kg/m 2 , who were not affected by diabetes mellitus, hypertension or dyslipidaemia, 5% weight loss was associated with normalisation of blood pressure in both genders, even though the volume of this loss was associated with a significant decrease in blood pressure in men only. In the study by Cochrane et al [ 46 ], 26% of modifiable CVD risk was associated with high blood pressure.…”
Section: Discussionmentioning
confidence: 99%